Effect of Thermoelectrics as a Cooling System on Photovoltaic Efficiency and Economic Analysis - Abdul Hakim, Muhammad Fuad; Nurhilal, Otong (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2025)
Photovoltaics (PV) are one way to utilize sunlight as a renewable energy source. However, currently commercially available PV is only capable of converting around 15% of sunlight into electrical energy, while the rest is converted into heat which can increase the temperature of the PV itself. On the other hand, increasing PV temperature results in a decrease in the output power produced and ultimately reduces efficiency. Therefore, efforts are needed to reduce the PV temperature in order to increase efficiency, namely by adding a cooling system to the PV. One PV cooling system that tends to be new is the thermoelectric cooler (TEC). However, the use of TEC will increase the cost of TEC components and electrical power. This research aims to determine the effect of using TEC as a cooling system on PV efficiency and its economic analysis. Two PV units are used, with a TEC cooling system and without a cooling system which is used as a reference. Experiments were carried out outdoors in direct sunlight. The results showed that the use of TEC as a cooling system was able to increase PV efficiency by 6.45%. Meanwhile, from an economic analysis using levelized cost of energy (LCOE), it was found that, although it can increase PV efficiency, the use of TEC as a cooling system has an LCOE of Rp. 15,871/kWh, meaning that using TEC is more expensive than LCOE without a cooling system, namely only Rp. 5,350/kWh.